Importance of Several Components of Annual Report to the Investors: A Study on the Northern Part of Bangladesh - Roy, Brazendra Nath; Dash, Purbasha (International Journal of Business, Economics, and Social Development, 2023)
This study examines the perceived usefulness of several components of the annual reports in the decision-making process of investors in making investment decisions. Corporations provided their financial information i.e financial result, financial conditions, and distributions to shareholders etc. to the users through corporate annual report. The main objective of the study is to measure the level importance of the several parts of annual report in providing useful information to the investors. A well-organized questionnaire was used to collect data from the respondents. Descriptive statistics, reliability tests, correlation, regression, etc., were applied to detect the result of the study. The development of the survey indicates that the annual report provides the required information to the investors for their rational investment decision, but some components of the annual report are not helpful at all to the investors. Balance Sheet, Statement of Cash Flow, Notes to the Financial Statements, Auditors Report, Five Years Financial Highlights, and Income statement were providing more valuable information regarding investment. The findings of the study will encourage preparers to provide reliable information as well as encourage users in using yearly report of corporations.